2018
DOI: 10.1093/eurheartj/ehy585
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of endurance, interval, and resistance training on telomerase activity and telomere length in a randomized, controlled study

Abstract: AimsIt is unknown whether different training modalities exert differential cellular effects. Telomeres and telomere-associated proteins play a major role in cellular aging with implications for global health. This prospective training study examines the effects of endurance training, interval training (IT), and resistance training (RT) on telomerase activity and telomere length (TL).Methods and resultsOne hundred and twenty-four healthy previously inactive individuals completed the 6 months study. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 45 publications
8
137
2
8
Order By: Relevance
“…Regular physical activity or endurance exercise training can positively alter the human gut microbiota by increasing bacterial diversity, increasing faecal concentrations of short-chain fatty acids and increasing the proportion of healthy bacterial species (Allen et al 2018;Bressa et al 2017;Estaki et al 2016). A recent study on endurance training has shown that exercise increases telomerase activity and length, whereas resistance training did not show these effects (Werner et al 2019). Ideally, a combination of resistance and endurance training should be implemented (Reiner et al 2019).…”
Section: Physical Activitymentioning
confidence: 99%
“…Regular physical activity or endurance exercise training can positively alter the human gut microbiota by increasing bacterial diversity, increasing faecal concentrations of short-chain fatty acids and increasing the proportion of healthy bacterial species (Allen et al 2018;Bressa et al 2017;Estaki et al 2016). A recent study on endurance training has shown that exercise increases telomerase activity and length, whereas resistance training did not show these effects (Werner et al 2019). Ideally, a combination of resistance and endurance training should be implemented (Reiner et al 2019).…”
Section: Physical Activitymentioning
confidence: 99%
“…Our results also suggest that environmental factors with the potential to prevent premature telomere shortening may have positive influences on hippocampal neurogenesis and cognitive function. Intriguingly, environmental interventions shown to reduce the rate of cognitive ageing (80), including exercise and energy restriction, have positive effects on both peripheral telomere length in humans (15,81,82) and hippocampal neurogenesis in animal models (83,84). Furthermore, diets rich in omega-3 fatty acids and antioxidants, have been associated with both increased rates of hippocampal neurogenesis and longer telomeres (32,85,86), as have some drugs, such as resveratrol and lithium (14,(87)(88)(89).…”
Section: <<< Figure 2 >>> (Ii) Old Hippocampal Progenitor Cells Exhibmentioning
confidence: 99%
“…Daneben führt sportliche Aktivität zu einer höheren Blutverteilung in der arbeitenden Muskulatur, der transportierte Sauerstoff in den Arterien wird ökonomischer genutzt und die Herzfrequenz bei Belastung und in Ruhe herabgesetzt [3]. Auf zellulärer Ebene konnte gezeigt werden, dass die Telomeraseaktivität mit einem regelmäßig durchgeführten Ausdauertraining steigt und damit die Zellalterung verlangsamt [21]. Sportlich Aktive profitieren insgesamt von einem 30 % niedrigeren Gesamtsterblichkeitsrisiko im Vergleich zu sportlich Inaktiven [22].…”
Section: Theorieunclassified